Portugal SB07 Sustainable Construction, Materials and Practices Challenge of the Industry for the New Millennium (Part 1) - Bragança, Luis (IOS Press, 2013)
Article 7 of the EU Energy Performance of Buildings Directive requires Member States to implement energy certification for buildings, and particularly for large public buildings, requires an energy certificate to be displayed in public. This paper outlines a simplified procedure for the certification of existing public buildings based on measured energy consumption, which is applicable even in countries where information on the building stock is not currently available. Energy consumption data collected for a number of buildings is used to develop energy benchmarks for typical and good practice energy performance. The rating procedure is based on a comparison between the energy consumption of each building and the derived benchmarks; a process that is illustrated in a sample of 88 Irish primary schools. The paper concludes with a discussion on the next steps to a more detailed measured rating procedure.